HUBUNGAN ANTARA PENDIDIKAN KESEHATAN DAN KEPUASAN PASIEN DIABETUS MULLITUS DI RUANG RAWAT RUMAH SAKIT PERSAHABATAN TAHUN 2011 - Suratun, -; Manurung, Santa; Sumartini, Mamah (Jurnal Ilmiah Widya, 2014)
The planning for patient Discharge Planning including special program to give health education which aims to prepare the patient to go home and to continue the treatment program at home (Potter & Perry, 2005:3). In Persahabatan hospital (Jakarta) the health education been conducted so far but, in implementation has not been maximized yet. The result from surveys on the patient satifaction in Persahabatan hospital was 77,1%. The result still lower in compare to the minimum standard of Indonesia hospital service which found to be 90% (Depkes RI, 2007:12). This research aim to study the relationship health education during patient Discharge Planning with patient satisfaction in Persahabatan hospital. The research was a quantitatif study using descriptive desain. Variables to be observed were the independent variables: health education for DM Discharge patients and the dependent variable: patient satisfaction (reliability, response, guarantee, direct evidence and caring). The sample used here is all DM patient which have been taken care of in Persahabatan hospital during December 2011 until January 2011 which the total number of 76 patients. The result of the study indicated that the health education program have a to find out relationship with patient satisfaction.